2008
DOI: 10.1111/j.1540-8175.2007.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between NT‐pro BNP Levels and Early Mitral Annulus Velocity (E′) in Patients with Non–ST‐Segment Elevation Acute Coronary Syndrome

Abstract: NT-pro BNP levels are elevated in acute coronary syndromes, even in the absence of significant necrosis. Of all echocardiographic parameters investigated, only E' and the EF correlated with the levels of NT-pro BNP in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(58 reference statements)
1
2
0
1
Order By: Relevance
“…21 In the group of patients with non-ST segment elevation coronary syndromes, EF and E/e' were the only echocardiographic parameters correlated with NT pro-BNP levels. 23 In our group of patients these parameters revealed significant correlation not only dur-ing acute phase of myocardial infarction but also after 1-year follow-up.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…21 In the group of patients with non-ST segment elevation coronary syndromes, EF and E/e' were the only echocardiographic parameters correlated with NT pro-BNP levels. 23 In our group of patients these parameters revealed significant correlation not only dur-ing acute phase of myocardial infarction but also after 1-year follow-up.…”
Section: Discussionsupporting
confidence: 49%
“…NT pro‐BNP is important prognostic factor in cardiovascular diseases and peptide serum concentration monitoring is a widely used diagnostic tool in heart failure patients 21 . In the group of patients with non‐ST segment elevation coronary syndromes, EF and E/e’ were the only echocardiographic parameters correlated with NT pro‐BNP levels 23 . In our group of patients these parameters revealed significant correlation not only during acute phase of myocardial infarction but also after 1‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have demonstrated that the levels of BNP and NT-proBNP are powerful prognostic markers across a spectrum of acute coronary syndromes (15), from unstable angina and non-ST elevation myocardial infarction to ST elevation myocardial infarction (1618), as well as in patients with stable angina pectoris (19,20) and even in the absence of significant necrosis (21). BNP and NT-proBNP are present in human coronary arteries (22) and are associated with the extent and severity of coronary atherosclerotic lesions (23). The observations of the present study revealed a similar correlation; the proportion of patients with myocardial infarction was significantly higher in the BNP >100 pg/ml group as compared with the BNP ≤100 pg/ml group (P=0.039).…”
Section: Discussionmentioning
confidence: 99%
“…Σε ασθενείς με ασταθή στηθάγχη βρέθηκε πως τα αρχικά επίπεδα ΒΝΡ ήταν υψηλότερα σε εκείνους που απεβίωσαν, συγκριτικά με τους επιβιώσαντες [204][205][206][207] . Τέλος, σε ασθενείς με έμφραγμα με ή χωρίς ανάσπαση του ST διαστήματος τα υψηλότερα επίπεδα ΒΝΡ συσχετίζονταν με αυξημένη πιθανότητα θανάτου ή καρδιακής ανεπάρκειας, ανεξάρτητα από άλλους προγνωστικούς παράγοντες, όπως το κλάσμα εξώθησης [208][209][210][211][212] .…”
Section: οξέα στεφανιαία σύνδρομαunclassified